2012
DOI: 10.4028/www.scientific.net/amr.430-432.434
|View full text |Cite
|
Sign up to set email alerts
|

Research on Hardening Mechanism of Cement-Emulsified Asphalt-Epoxy Resin

Abstract: This article researched the cementation and hardening mechanisms of cement asphalt emulsion and waterborne epoxy mortar by using the XRD, and heat of hydration testing methods. The results of this study show that the mixture of cement with epoxy and cement- asphalt-epoxy are endothermic reaction. There are occurring endothermic reactions between cement with epoxy. The waterborne epoxy resin and basic structure unit of ettringite [Ca3Al(OH)6•12H2O] were reacted and formed Ca-complex at earlier period of hydrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…The shear strength properties of the epoxy-emulsified asphalt were tested, indicating that the shear strength decreased with an increase in temperature, owing to decreased adhesion [25]. Microscopic analysis of a composite system containing waterborne epoxy resin-cement-emulsified asphalt showed that the material demonstrated good flexibility, high-temperature stability, and high bond strength [26][27][28]. A new type of fog-sealing layer asphalt was prepared by modification and emulsification, and its performance was analyzed [29].…”
Section: Introductionmentioning
confidence: 99%
“…The shear strength properties of the epoxy-emulsified asphalt were tested, indicating that the shear strength decreased with an increase in temperature, owing to decreased adhesion [25]. Microscopic analysis of a composite system containing waterborne epoxy resin-cement-emulsified asphalt showed that the material demonstrated good flexibility, high-temperature stability, and high bond strength [26][27][28]. A new type of fog-sealing layer asphalt was prepared by modification and emulsification, and its performance was analyzed [29].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, they have been conventionally modified by different types of modifiers . As one of these modifiers, waterborne epoxy resin as a new type, which inherits excellent high acid resistance (Abd El-Rahman et al, 2017), mechanical performance (Qian et al, 2012), bond strength and high-temperature stability (Zhang et al, 2017) from epoxy resin, shows advantages like free of tackiness and environmentally friendliness than oil-based epoxy resin (Zhang et al, 2017), so it has been recently revealed as the modifier of emulsified asphalt in cold patch engineering (Zhang et al, 2017;Zhang and He, 2007;Ding et al, 2011;Shen et al, 2012; Chen and Chen, 2016), and emulsified asphalt modified by waterborne epoxy resin has been studied in recent years. Zhang and He (2007) studied adhesion and various performances of evaporation residues and durability of emulsified asphalt mixed by the compound of waterborne epoxy resin and styrene-butadiene rubber (SBR), and results reveal that this emulsified asphalt showed better road performances than those of ordinary asphalt emulsion and SBR modified asphalt emulsion.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of 2011) show that performances of a cementbased material reinforced by epoxy resin and emulsified asphalt (CAE) were good, especially rutting deformation at high temperature and adhesive strength with steel blocks; furthermore, the microscopic feature of CAE was related to its development of performances. Shen et al (2012) researched cementation and hardening mechanisms of CAE, and results show that the crosslinked action of the bonding system of asphalt binder and cement hydration products was not obvious, but the bonding system was enhanced by epoxy hardening products, because they were interleaved with cement hydration products, and reinforced asphaltic material.…”
Section: Introductionmentioning
confidence: 99%